EFEK MENULIS PENGALAMAN EMOSIONAL TERHADAP STRES PADA PENGHUNI LEMBAGA PEMASYARAKATAN - Nur Rahmi Hasyim (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2015)
Stress isexperienced by all people, no body but prison residents, have experience changes of life withthe pressurefrom environmentthataffectingmental health.Therefore need psychological assistence through writing experience emotional. The research goal to want effect of writing emotional experienceameans ofpsychologicalassistancethrough thewritingof everydayemotional experiences. This studyaims to determinethe effect ofwritingto stresstheemotionalexperience ofprisonresidents. Methods ofresearch usingexperimentalpre-test post-test controlgroupdesignwithparticipants in prison of Malang. The instrument usedis thestress scale. Dataanalysisusing aparametrictechnique.Dataanalysisusing paired sample t-test. The results showedvaluesof sum t = 6.818 and significant 0.000. Under thesecond testshowsthe research hypothesisis accepted,whichmeans writingan emotional experiencehas asignificant effectof stress on theresidents ofcorrectional institutions.